A prospective 14‐year longitudinal follow‐up of dementia in persons with Down syndrome. (31st July 2013) - McCarron, M.; McCallion, P.; Reilly, E.; Mulryan, N.
Abstract Background To examine dementia characteristics, age at onset and associated comorbidities in persons with Down syndrome. Method Seventy‐seven people with Down syndrome aged 35 years and older were followed longitudinally. The diagnosis of dementia was established using the modified International Classification of Diseases, Tenth Revision (ICD‐10) criteria and a combination of objective and informant‐based tests. Cognitive tests included the Test for Severe Impairment and the Down Syndrome Mental Status Examination; adaptive behaviour was measured using the Daily Living Skills Questionnaire. The Dementia Questionnaire for Mental Retarded Persons (DMR) was added to the test battery in 2005 and this study includes follow‐up data for this instrument. Results Over the 14‐year period the average age of diagnosis at 55.41 years (SD = 7.14) was in the higher range of previously reported estimates (51–56 years) and a median survival of 7 years after diagnosis. Persons with dementia in the sample were significantly older than persons without dementia. The presence of dementia was also associated with epilepsy and sensory impairments. Among instruments the DMR appeared most sensitive to tracking change in symptoms over time before diagnosis. Conclusion The previously reported high risk levels for dementia among people with Down syndrome was confirmed in these data as was the value of the instruments utilised in tracking decline and helping to confirm diagnosis even in persons with severe intellectual disability.